Molecular characterization of Hepatozoon canis in dogs from Colombia - Vargas-Hernandez, Giovanni [UNESP]; Andre, Marcos R. [UNESP]; Munhoz, Thiago D. [UNESP]; Faria, Joice M. L. [UNESP]; Machado, Rosangela Z. [UNESP]; Tinucci-Costa, Mirela [UNESP] (Springer, 2012)
Hepatozoonosis is a tick-borne disease whose transmission to dogs occurs by ingestion of oocysts infected ticks or feeding on preys infested by infected ticks. Until now, there is no previous report of molecular characterization of Hepatozoon sp. in dogs from Colombia. EDTA blood samples were collected from 91 dogs from central-western region of Colombia (Bogota, Bucaramanga, and Villavicencio cities) and submitted to 18S rRNA Hepatozoon sp. PCR and blood smears confection. Phylogenetic analysis was used to access the identity of Hepatozoon species found in sampled dogs. From 91 sampled dogs, 29 (31.8%) were positive to Hepatozoon sp. (25 dogs were only positive in PCR, 1 was positive only in blood smears, and 3 were positive in both blood smears and PCR). After sequencing, the found Hepatozoon sp. DNA showed 100% of identity with Hepatozoon canis DNA isolates. The phylogenetic tree supported the identity of the found Hepatozoon sp. DNA, showing that the isolates from Colombia were placed in the same clade than other H. canis isolates from Venezuela, Spain, and Taiwan. This is the first molecular detection of H. canis in dogs from Colombia.
Keywords: Hepatozoon canis; Dog; Molecular characterization; Colombia